A 28-Year-Old Woman with Down Syndrome, Congenital Heart Disease, and a History of Knee Surgery and Plantar Fasciitis, with Hallux Abducto Valgus (Bunion) and Lapiplasty Three-Dimensional Correction Surgery - Simón-Pérez, Eduardo; Jiménez-Martín, Rodrigo; Cicchinelli, Luke D; Fernández-Yagüe, Javier; Simón-Pérez, Clarisa; Páez-Moguer, Joaquín; Cortés-Rodríguez, Antonio; Castillo-Domínguez, Alejandro (Internacional Scientific Information, 2023)
Background: Tarsometatarsal joint (TMJ) arthrodesis is common method used for correcting hallux abductus valgus (HAV). Its popularity has grown due to studies revealing HAV’s triplanar deformity with frontal plane rotation. This case report presents a 28-year-old woman with Down syndrome, congenital heart disease, and a history of knee surgery and plantar fasciitis, with severe HAV deformity and flexible valgus flatfoot associated with ligamentous hyperlaxity. Case Report: Examination revealed severe foot deformities, and radiographic studies confirmed the condition. A surgical intervention was planned, and the patient’s cardiologist confirmed she was fit for the procedure. The modified Lapidus technique with frontal plane rotational correction included realigning the metatarsal joint, resecting spurs, osteosynthesis material, and arthrosis in the sinus tarsi. After surgery, the patient underwent a recovery period without support for 8 weeks and received appropriate medical care. Radiographs showed successful alignment, and the patient gradually resumed her daily activities. The patient had an uneventful recovery, and postoperative radiographs showed good alignment in all planes. Conclusions: The hyperlaxity associated with Down syndrome makes the incidence of HAV more frequent, and TMJ fusion is preferable to correction by osteotomy. The modified Lapidus technique with frontal plane rotational correction could be a good technique to achieve satisfactory correction in patients with severe HAV deformity and flexible valgus flatfoot associated with ligamentous hyperlaxity. TMJ fusion is indicated when severe or recurrent rotational component is observed in X-rays
Keywords: Down, Síndrome de; Cardiopatía congénita; Rodillas - Cirugía; Arthrodesis; Down Syndrome; Flatfoot; Hallux Valgus